2013
DOI: 10.1002/asi.22932
|View full text |Cite
|
Sign up to set email alerts
|

Is the world getting flatter? A new method for examining structural trends in the news

Abstract: In this article, we propose a new method to analyze structural changes in networks over time and examine how the representation of the world in two leading newspapers, the New York Times and Der Spiegel, has changed during the past 50 years. We construct international networks based on the co‐occurrences of country names in news items and trace changes in their distribution of centrality over time. Supporting previous studies, our findings indicate a consistent gap between the most central and the least centra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…This decision to strictly focus on country names and not include nationalities was based on the fact that it would complicate the translation process due to divergent grammatical rules in different languages. Previous studies (Segev, 2010;Segev and Blondheim, 2013a;Segev, Sheafer and Shenhav, 2013), however, show that focusing on country names in a high volume of news items provides a very good proxy of the actual attention a country gives to another in its news outlets.…”
Section: News Collection and Analysismentioning
confidence: 99%
“…This decision to strictly focus on country names and not include nationalities was based on the fact that it would complicate the translation process due to divergent grammatical rules in different languages. Previous studies (Segev, 2010;Segev and Blondheim, 2013a;Segev, Sheafer and Shenhav, 2013), however, show that focusing on country names in a high volume of news items provides a very good proxy of the actual attention a country gives to another in its news outlets.…”
Section: News Collection and Analysismentioning
confidence: 99%
“…Network analysis has been widely used in academic studies of international relations and cross-cultural communication (see Barnett & Park, 2005, 2014Chang, Himelboim, & Dong, 2009;Kim & Barnett, 2000;Kim & Barnett, 2007;Rosen, Barnett, & Kim, 2011;Segev, Sheafer, & Shenhav, 2013;Park, Barnett, & Chung, 2011). In addition, network analysis has been used in the public sector to bridge the gap between practice and planning (Guhaa & Chakrabartib, 2014).…”
Section: Applying Network Analysis To International Relationsmentioning
confidence: 99%
“…Therefore, developing personalized content systems requires not only detecting and tracking current interests but also predicting what content users would be interested in the future (Mele, Bahrainian, & Crestani, 2019) or at least what related future content (Toraman & Can, 2017) a person might prefer. Although content producing organizations naturally attempt to do this, studies on online news have shown that most news content focuses on consistent themes (i.e., United States, Western Europe), although this is undergoing a change with shifts in news content to Middle Eastern, and Asian countries (Segev, Sheafer, & Shenhav, 2013).…”
Section: Review Of Literaturementioning
confidence: 99%